2002
DOI: 10.1177/154411130201300607
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pulpal Reactions to Restorative Procedures, Materials, Pulp Capping, and Future Therapies

Abstract: Every year, despite the effectiveness of preventive dentistry and dental health care, 290 million fillings are placed each year in the United States; two-thirds of these involve the replacement of failed restorations. Improvements in the success of restorative treatments may be possible if caries management strategies, selection of restorative materials, and their proper use to avoid post-operative complications were investigated from a biological perspective. Consequently, this review will examine pulp injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 87 publications
1
89
0
10
Order By: Relevance
“…Progenitor cells of new odontoblast-like cells assumed as cells from the subodontoblast layer or pulp fibroblasts. 17 In the de-differentiation process, the odontoblast cell is not turned young and pluripotent, but still unipotent and just divide from the cell with the same structure and function with the related cell. There are two mechanisms of reparative dentinogenesis.…”
mentioning
confidence: 99%
“…Progenitor cells of new odontoblast-like cells assumed as cells from the subodontoblast layer or pulp fibroblasts. 17 In the de-differentiation process, the odontoblast cell is not turned young and pluripotent, but still unipotent and just divide from the cell with the same structure and function with the related cell. There are two mechanisms of reparative dentinogenesis.…”
mentioning
confidence: 99%
“…37 During reactionary dentinogenesis (Figure 1), solubilized TGF-βs may be able to diffuse to the odontoblasts and pulpal cells localized beneath the damaged region and signal the up-regulation of these cells' secretory activity. 27 This upregulation of surviving odontoblasts will lead to focal secretion of new matrices at the pulp-dentin interface. 2 Quite a few studies have demonstrated that TGF-β stimulates the synthesis of extracellular matrices and also initiates odontoblast cytodifferentiation in vitro 38 and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these primary cells must be replaced by a new generation of odontoblast-like cells. 27 Therefore, the formation of reparative dentin is a complex sequence of biological process, which is dependent on multiple factors, including the presence of responsive progenitor cells as well as the appropriate inductive molecular signals for induction of proliferation, migration, and differentiation of the new generation of odontoblast-like cells. The derivation of the progenitor cells for these odontoblast-like cells remains unclear although they may be variable.…”
Section: Reactionary Dentinogenesismentioning
confidence: 99%
“…This is still a matter of controversy and a few reports still consider that the pulp reaction to adhesive systems is generally minimal (Murray et al 2002, Murray et al 2003. Improvements of resin-containing materials and bonding agents and techniques have reduced the significance of shrinkage and gaps at the interface, which may be less than 1µm (Hashimoto et al 2004).…”
Section: The Role Of Bacteriamentioning
confidence: 99%